Between Rhetoric and Practice Explaining the Gap Between Role Conception and Performance in Journalism - Mellado-Ruiz, C (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2014)
A large body of research in journalism studies has analyzed which social and political roles news professionals consider they must fulfill in society. These studies are based on the assumption that role conception influences news content. However, the gap between ideals and practice is inevitable, since the constraint to which journalists are exposed limits the possibility of living up to their normative standards. While recent studies have addressed the relationship between ideals and practice by studying whether journalists with different roles report differently, we know less about the gap between the two. By comparing the role conception of journalists with the news stories they produce, we address the (dis)connection between roles and content as a gap, analyzing which roles render a larger distance and also which journalists are more likely to put their ideals into practice. The findings show a significant gap between role conception and performance, particularly for the service, civic and watchdog roles. Greater perceived autonomy leads to a smaller gap, while economic and political influences as well as belonging to a beat increase the gap. Likewise, the gap varies significantly between journalists working at the quality and the popular press.